(untitled) (XXI Century. Spanish Literature and Culture, 2008)
Although Spain’s transition to democracy has long been considered a model for other nations leaving a dictatorial regime, critical voices in recent years there have been more critical voices that have expressed the contradictions and imperfections in the aforementioned process, among these the pact of historical oblivion. Since the last decade however, there has been an abundance of literary, cinematic and television texts that retakes a nostalgic vision of the Transition. This work proposes a critical reading of the text, which will be served by the following techniques: melodrama and serial literature. These will be used to offer an image of the historical process as a collective and coherent story that falsely reinforces the idea of a model Transition.